Perancangan Interior Kenjeran Expo di Surabaya - Fabianus Yanuar; Andereas Pandu Setiawan (Intra, 2016)
Amusement Park Attraction Kenjeran Beach is a beach located in the Village District of Bulak Kenjeran and started up in 1968 with an area of ± 4.3 ha to 2.3 ha of productive land is used as an area tujuanwisata, infrastructure and parking space. THP Kenjeran management conducted by the Office of Technical Implementation Unit Kenjeran Beach Amusement Park in the Department of Culture and Tourism of the city of Surabaya. Tarikwisata objects and targets that can be used as a recreation destination for tourists who want to visit. The concept of adopting design styles Industrial - Minimalism lifting the industrial city of Surabaya as applied in a way that serves the typical tourist attractions Surabaya.